Peranan Sumber Daya Manusia dan Presentasi (Presenter) Dalam Memasarkan Produk Pendidikan di Lembaga Pendidikan dan Pengembangan Profesi Nusantara - D Purnomo; Nu Haris Effendi (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2021)
To win business competition either in the field of education or other fields businesses must carry out various marketing strategies such as: product strategy, pricing strategy, promotional strategy, and strategy and presentation of Manusa resources. The last two strategies are important strategies in recruiting prospective students (customers), Presenter's performance can be measured through the ratio of consumers who come to then enroll and the next who register (become students). The problem at the moment is that thebalancebetween consumers who come, consumers who sign up and consumers who are accepted is poorly maintained . Based on the above problems, the author chose the Nusantara Professional Education and Development Institute (LP3N) as the object of research, because LP3N is an educational institution engaged in the development of Human Resources (HR) that produces ready-to-eat labor. The purpose of this research is prioritized to know the extent of the role of human resources and presentations (presenters) in marketing educational products in order to attract students in the process of admission of new students conducted by educational institutions and professional development of the archipelago (LP3N). In addition, in order to be utilized by the Nusantara Professional Education and Development Institute (LP3N) in taking policy in its marketing activities. In this study using quantitative method where this research is intended to describe and analyze the role of presenters in marketing educational products in educational institutions and professional development of the archipelago. While in the calculation process using SPSS Version 24.Keywords : Consumers, Human Resources, Marketing Strategy, Performance, Presenter.